Effect of Loose Smut Pathogen on Plant Growth and Seed Quality Parameters of Wheat - S.S. GAURAV,; ASHOK GAUR,; K. KANT,; OMKAR SHARMA, (Seed Research, 2026)
The investigation were carried out to evaluate the effect of loose smut pathogen on growth attribute and seed quality parameter in five cultivars namely Sonalika, PBW 65, PBW 343,VL-421 and HD 2687. The total number of tillers in infected plant were less as compared to healthy plants in all the cultivars, though the differences were significant only in susceptible cultivars i.e. Sonalika, HD 2687 and PBW 343. Length of peduncle in case of smutted plants was significantly reduced as compared to healthy plants, though the differences were more apparent in susceptible cultivars. Infection by Ustilago segetum var. tritici in seed results in reduction of 1000-grain weight and germination as compared to healthy seeds in all cultivars, but reduction was more apparent in susceptible cultivars.